Design of Ni3N/Co2N heterojunctions for boosting electrocatalytic alkaline overall water splitting. Issue 16 (13th April 2021) - Wen, Yan; Qi, Jingyao; Wei, Peicheng; Kang, Xu; Li, Xin
Abstract : The heterojunction structure accelerates the overall water splitting for transition metal nitrides. Pyridine nitrogen and metal ions that act as catalytic sites synergistically promote the electrocatalytic process. Abstract : Transition metal nitrides (TMNs) are one of the most promising electrocatalysts for overall water splitting, although they are still limited by the requirement of rapid kinetics and high sustainable driving. Herein, we present a facile strategy for efficiently designing heterostructure electrocatalysts based on density functional theory calculations. The construction of bi-functional electrocatalysis is described by introducing nitrogen to tailor a unique flower-like nickel–cobalt layered double hydroxide (N–NiCo-LDH) for accelerating hydrogen and oxygen evolution reactions (HERs and OERs). The electron redistribution at the Ni3 N/Co2 N heterojunction interface favors the energy barrier for HERs/OERs and, thus, improves the electrocatalytic activity. As such, the N–NiCo-LDH shows an ultra-low overpotential of 35 mV at 10 mA cm −2 for HERs and the Tafel slope is 34 mV dec −1, while it requires only 1.55 V to deliver a current density of 10 mA cm −2 for alkaline overall water splitting without iR compensation, which manifests one of the best non-noble bi-functional electrocatalysts. Moreover, we controllably adjusts the relative concentrations of pyridine nitrogen and metal ions in the N–NiCo-LDH via blocking and complexing experiments, directly verifying that pyridine nitrogen and metal ions as catalytic sites synergistically promote the electrocatalytic process, which will provide an in-depth insight into the corresponding synergistic mechanism.